Measuring the relationship between workplace opportunities and motivation among women in the technology industry - Jess Murdoch (Fields, 2021)
The issue of gender imbalance is one that affects almost all industries but is particularly prevalent within technology and engineering. Just 14.4% of the overall science, technology, engineering and maths (STEM) workforce in the UK are female (ONS, 2015), and with many years of government efforts having been made to increase the interest of school age girls in STEM subjects, it would be thought that the figures in the workplace would be balancing out. This does not appear to be the case, however.